Tehnično ekonomska analiza izrabe odpadne toplote pri hlajenju strojev - Kronovšek, Sašo (Strojniški vestnik, 1999)
In industry and trade we usually encounter forming procedures where thermal processes take place at the temperature different from the surrounding one. In most of these cases there are necessities to supply heat on one hand and to take it away on the other hand. Until now most of such cases were solved with a simple circulating cooling, especially such with possibility of reusing surplus heat, there is necessary to test possible constructions from the technological as from the economic point of view. Different cooling existing cooling of the plastic mold filling machine.
Keywords: hlajenje strojev; toplota odpadna; brizganje polimerov; analize ekonomske; hlajenje; toplotna bilanca; polimeri; brizganje